Price of Four Loko in Large U.S. Cities, 2018. (31st May 2019) - Rossheim, Matthew E.; Thombs, Dennis L.; Treffers, Ryan D.; Trangenstein, Pamela J.; McDonald, Kayla K.; Ahmad, Reema; Siklo, Sieka S.; Gonzalez‐Pons, Kwynn M.; Suzuki, Sumihiro; Jernigan, David H.
Abstract : Background: Supersized alcopops are flavored alcoholic beverages that contain up to 5.5 standard alcoholic drinks in a single can. Limited research suggests Four Loko—the most commonly consumed supersized alcopop by underage drinkers—is among the least expensive ready‐to‐drink alcohol products on the U.S. market. This is a public health concern because alcohol prices are inversely associated with consumption and related harms, particularly among youth. This study investigated Four Loko's retail price per volume of alcohol in large U.S. cities. Methods: This study used multistage random sampling to collect data in the largest city of each state and Washington, DC. A simple random sample of 5 ZIP codes from each city was selected and entered into Four Loko's website product locator. Within ZIP codes, up to 4 stores were randomly selected and contacted by telephone. Retailers were interviewed about Four Loko in regard to: availability, volume, alcohol by volume (abv), price for 1 can, and discounts for purchasing more than 1 can. Results: The sample included 344 retail stores with Four Loko in stock. Average price per standard alcoholic drink (i.e., 14 g of absolute alcohol) was $0.54 for Four Loko products. Taking into account volume, price, and discounts, an average of 17 standard alcoholic drinks could be purchased via Four Loko with $10. Adjusted analysis using linear regression showed that availability of bulk price discounts and higher abv (14% vs. 12%) were associated with lower price per drink. Conclusion: This study verifies that Four Loko is among the least expensive ready‐to‐drink alcohol available for purchase in the United States. Given that consuming a single supersized alcopop constitutes binge drinking and is therefore unsafe, regulatory agencies should consider a variety of steps to reduce the availability and abv of these products and increase their retail price in order to reduce and prevent unsafe alcohol consumption.